"Venezia 1625" sonate, symphonie, ciaccone, canzone & toccate ; [CD] - Uccellini, Marco 1603-1680; Storace, Bernardo; Fontana, Giovanni Battista 1589-1631; Merula, Tarquinio 1594-1665; Rossi, Salamone 1570-1630; Castello, Dario 1621-1644; Piccinini, Alessandro 1566-1638 (Harmonia Mundi, 2009)
Sonaten, Sinfonien, Ciacconen, Canzonen und Toccaten des frühen 17. Jahrhunderts, / pr